The Psychological Conflict of Laura in Carmilla (1872) by Joseph Sheridan Le Fanu - Yasmin Nadhira; M. Bahri Arifin; Setya Ariani (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study analyzes the novella Carmilla (1872) to explore Laura's psychological conflict, a young woman living in isolation with her father in a secluded castle. Her encounter with Carmilla, a mysterious and affectionate stranger later revealed to be a vampire, becomes the catalyst for the psychological conflict. This study analyses how Laura's psychological conflict is represented using Kurt Lewin’s theory of psychological conflict. Employing a descriptive qualitative method, the research interprets the hidden meaning behind Laura’s emotional responses, decisions, and motivations when facing complex and dangerous situations. The findings reveal that Laura experiences all three types of psychological conflict, which are the approach-approach conflicts arising from her longing for companionship and her safety with and without her friend, avoidance-avoidance conflicts connected to the nightmare she experienced, and the dilemma of whether to reveal them to her father, and the most dominant type is approach-avoidance conflict, marked by Laura’s struggle to reconcile her affection, trust, and desire for emotional connection with fear, uncertainty, and betrayal. These conflicts intensify as Laura becomes increasingly aware of Carmilla’s true nature. In resolving her psychological conflict, the concept of valence is used to understand which choices Laura considers to have a more desirable and beneficial outcome (positive valence) and which have more undesirable outcomes and should be avoided (negative valence